Prevalence of low bone mineral density in children and adolescents with celiac disease under treatment - Motta, Maria Eugênia Farias Almeida; Faria, Maria Eduarda Nóbrega de; Silva, Gisélia Alves Pontes da (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Low bone mineral density may be a finding among children and adolescents with celiac disease, including those undergoing treatment with a gluten-free diet, but the data are contradictory. The aim of this study was to determine the frequency of bone mineral density abnormalities in patients on a gluten-free diet, considering age at diagnosis and duration of dietary treatment. DESIGN AND SETTING: Cross-sectional prevalence study at the Pediatric Gastroenterology Outpatient Clinic of Instituto Materno Infantil Professor Fernando Figueira. METHODS: Thirty-one patients over five years of age with celiac disease and on a gluten-free diet were enrolled. Bone mineral density (in g/cm2 ) was measured in the lumbar spine and whole body using bone densitometry and categorized using the criteria of the International Society for Clinical Densitometry, i.e. low bone mineral density for chronological age ≤ -2.0 Z-scores. Age at diagnosis and duration of dietary treatment were confirmed according to the date of starting the gluten-free diet. RESULTS: Low bone density for chronological age was present in 3/31 patients in the lumbar spine and 1/31 in the whole body (also with lumbar spine abnormality). At diagnosis, three patients with low bone mineral density for the chronological age were more than 7.6 years old. These patients had been on a gluten-free diet for six and seven months and 3.4 years. CONCLUSION: Pediatric patients with celiac disease on long-term treatment are at risk of low bone mineral density. Early diagnosis and long periods of gluten-free diet are directly implicated in bone density normalization.